Importance of sympathetic activation for the expression of Na+-Ca2+ exchanger in end-stage failing human myocardium - Schillinger, W.; Schneider, H.; Minami, K.; Ferrari, R.; Hasenfuss, G. (European heart journal, 2002)
Aims In end-stage heart failure, an alteration in the expression of the Na+-Ca2+ exchanger has been reported. Regulation of its expression is largely unknown. We sought to find out whether Na+-Ca2+ exchanger in human heart failure is regulated by sympathetic activation. In addition, since Na+-Ca2+-exchange is electrogenic, we conjectured whether increased expression of Na+-Ca2+ exchanger is associated with an increased incidence of cardiac arrhythmias. Methods and Results Twenty-three patients suffering from end-stage cardiac failure were examined in the hours preceding cardiac transplantation. Plasma levels of norepinephrine, epinephrine, atrial natriuretic peptide, renin activity, aldosterone, tumour necrosis factor (TNF)-α, and TNF-receptors were measured. All parameters were elevated relative to 21 healthy control subjects. As determined by immunoblots, protein levels of the Na+-Ca2+ exchanger were increased by 56% and protein levels of sarcoplasmic reticulum (SR) Ca2+-ATPase were decreased by 20% in left ventricles of the explanted failing hearts. A significant correlation between protein and neurohumoral levels was exclusively found for the Na+-Ca2+ exchanger with norepinephrine (r=0·64;P =0·01). Recent Holter ECGs revealed that patients with sustained or non-sustained ventricular tachycardia (more than three consecutive beats) had significantly higher Na+-Ca2+ exchanger protein and plasma norepinephrine levels than patients with a maximum of two consecutive beats (Na+-Ca2+ exchanger: 109±10 vs 83±7, n=11 each, P<0·05; norepinephrine: 1359±159 vs 656±88pg.ml−1, n=9 each, P<0·001). Conclusions Sympathetic activation may enhance the expression of Na+-Ca2+ exchanger in end-stage heart failure. The data support the hypothesis that increased Na+-Ca2+-exchange could favour malignant ventricular arrhythmias. Copyright 2002 The European Society of Cardiology. Published by Elsevier Science Ltd. All rights reserved.